sheet

JP2025031196APending Publication Date: 2025-03-07NITERRA CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023137251
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0006】 本開示のシートは、リン脂質を含有する被覆層の担持量が高い。よって、本開示のシートは、高い組織修復性が見込める。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031196000001_ABST
    Figure 2025031196000001_ABST
Patent Text Reader

Abstract

To provide a sheet as an implant material having a coating layer including phospholipid on a surface thereof, the sheet with a higher amount of the coating layer.SOLUTION: A sheet 1 includes: a sheet base material 3 including at least one kind selected from a group composed of a collagen and a collagen derivative; and a coating layer 5 including phospholipid. The sheet has a maximum peak of a scattering intensity within a range of 1.2<q<1.4 of a wave number q(nm-1) by small angle X-ray scattering measurement, and has an intensity value defined by an expression (I) larger than 100 and smaller than 12000: intensity value=(Is-Isbg)÷(IG-I0)×100000 Expression (I).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a seat. [Background technology]

[0002] One of the most important things to do in managing patients immediately after surgery is to prevent blood clots and inflammation. Another important thing to do from the time of surgery until discharge is to repair the tissue around the surgical site. If wounds caused by incisions during surgery, sutures, and tissue repair around implants are delayed, patients will have to wait longer to start rehabilitation, and their hospital stay will be longer, which can be a major disadvantage for patients. Tissue regeneration is particularly slow around the jaw. Age also reduces the repair function. Therefore, implant materials that promote tissue repair around wounds generated when incising an affected area during surgery, suture sites, and implanted components are being studied. For example, Patent Document 1 studies an implant material with a coating layer containing phospholipids on its surface. This document discloses that a substrate coated with phosphatidylserine-containing liposomes (PSL) reduces the amount of inflammatory cytokines. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-94503 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the amount of phospholipid-containing coating layer supported is not necessarily sufficient, and improvement has been required. The present disclosure has an object to provide a sheet having an increased loading amount of a coating layer containing a phospholipid. The present disclosure can be realized in the following form. [Means for solving the problem]

[0005] [1] A sheet substrate containing at least one selected from the group consisting of collagen and collagen derivatives, and a coating layer containing a phospholipid, the sheet comprising: In small-angle X-ray scattering measurement, in the wavenumber region q (nm -1 ), having a maximum peak in the scattering intensity in the range of 1.2 < q < 1.4, a sheet in which the intensity value defined by the following formula (I) is greater than 100 and less than 12,000. Intensity value = (Is - Is bg ) ÷ (I G - I0) × 100,000... Formula (I) Is: The scattering intensity at the maximum peak in the range of 1.2 < q < 1.4 when the sheet is used as the measurement sample Is bg : The background scattering intensity at the same q as the maximum peak of the sheet when the sheet is used as the measurement sample I G : The scattering intensity at the same q as the maximum peak of the sheet when glassy carbon is used as the measurement sample I0: The scattering intensity at the same q as the maximum peak of the sheet when no measurement sample is placed [2] The sheet according to [1], wherein the phospholipid includes DOPS and DOPE-MAL. [3] A sheet substrate containing at least one selected from the group consisting of collagen and collagen derivatives, and a coating layer containing a phospholipid, the sheet comprising: The sheet, wherein the phospholipid includes DOPS and DOPE-MAL and does not include DOPC and DSPE-MAL. In addition, the preferred embodiments in [3] are as follows. In [3], it is preferable that the molar ratio of the DOPS: the DOPE-MAL is 40:60 - 60:40. In the above item [3], the phospholipid preferably forms a crosslinked liposome. In the above [3], the coating layer is It is preferable that the dispersion contains at least one compound selected from the group consisting of proteins and peptides having an isoelectric point of more than 7 when dispersed in water. In the above item [3], it is preferable that the coating layer contains protamine as the protein. [4] The phospholipids include DOPS and DOPE-MAL, The molar ratio of the DOPS:DOPE-MAL is The sheet according to [1] or [3], wherein the ratio of the thickness of the sheet to the thickness of the resin is 40:60-60:40. [5] The sheet according to [1] or [3], wherein the phospholipid forms a crosslinked liposome. [6] The coating layer is The sheet according to [1] or [3], comprising at least one compound selected from the group consisting of proteins and peptides having an isoelectric point of greater than 7 when dispersed in water. [7] The sheet according to [6], wherein the coating layer contains protamine as the protein. Effect of the Invention

[0006] The sheet of the present disclosure has a high loading amount of the coating layer containing phospholipids, and therefore the sheet of the present disclosure is expected to have high tissue repair properties. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a schematic diagram showing an estimated structure of a seat. [Diagram 2] 1 is a graph showing the results of small angle X-ray scattering measurements. [Diagram 3] This is a TEM image of a sheet using PSL-A. [Figure 4] TEM images of representative liposomes. [Diagram 5] A graph showing the number of lipid bilayers. [Figure 6] A graph showing the cavity volume within the liposome. [Figure 7] An image diagram of the multi-lamellar liposome structure. [Figure 8] A table and graph showing the results of quantifying the amount of liposome modification.

Mode for Carrying Out the Invention

[0008] Hereinafter, the present disclosure will be described in detail. In this specification, for a description using "-" for a numerical range, unless otherwise specified, it shall include the lower limit value and the upper limit value. For example, in the description "10 - 20", both the lower limit value "10" and the upper limit value "20" are included. That is, "10 - 20" has the same meaning as "10 or more and 20 or less".

[0009] <First Embodiment> 1. Sheet 1 A schematic diagram of an example of Sheet 1 is shown in FIG. 1. Sheet 1 includes a sheet base material 3 containing at least one selected from the group consisting of collagen and collagen derivatives, and a coating layer 5 containing a phospholipid. The surface of the sheet base material 3 is coated with the coating layer 5. In FIG. 1 showing a preferred embodiment of Sheet 1, liposomes formed containing a phospholipid indicated by reference numeral 7 and at least one compound selected from the group consisting of proteins and peptides indicated by reference numeral 9 are described, but the liposomes and this compound are optional components. Sheet 1 of the first embodiment has a maximum peak in the scattering intensity in the range of 1.2 < q < 1.4 in terms of the wave number region q (nm -1 ), and the intensity value defined by the following formula (I) is greater than 100 and less than 12000. Intensity value = (Is - Is bg ) ÷ (I G - I0) × 100000 … Formula (I) Is: The scattering intensity at the maximum peak in the range of 1.2 < q < 1.4 when Sheet 1 is used as the measurement sample Is bg : The background scattering intensity at the same q as the maximum peak of the sheet when Sheet 1 is used as the measurement sample I G : The scattering intensity at the same q as the maximum peak of Sheet 1 when glassy carbon is used as the measurement sample I0: The scattering intensity at the same q as the maximum peak of the sheet when no measurement sample is placed

[0010] Collagen is a protein derived from the extracellular matrix in the dermis, ligaments, tendons, bones, cartilage, etc. of vertebrates. Collagen has a right-handed helical structure composed of three peptide chains, and the amino acid residues constituting the peptide chain have a primary structure (collagen-like sequence) in which glycine residues are repeated every three residues. The type of collagen is not particularly limited. As the collagen, for example, type I, type II, type III, type V, type XI, etc. can be used. The main component of the sheet substrate 3 is preferably collagen. The main component refers to a substance with a content (mass%) of 50% by mass or more. In this embodiment, for example, as the sheet substrate 3, a collagen sheet with a dry thickness of 200 μm, a width of 15 mm, and a length of 20 mm (manufactured by Zimmer Biomet, BIOMEND (registered trademark)) can be used. The collagen derivative is not particularly limited. Examples of the collagen derivative include enzymatically degraded products of collagen (atelocollagen), succinoyl atelocollagen, myristoyl succinoyl atelocollagen, and water-soluble collagen. Atelocollagen is obtained by enzymatically removing 10 - 30 residues of telopeptides present at both ends of collagen (corresponding to a few percent of the whole collagen), and it is considered that the total charge does not change significantly between collagen and atelocollagen. Therefore, it is presumed that there is no significant difference in liposome modification, and it has the same properties as collagen and can be used in the same way as collagen.

[0011] The thickness of the coating layer 5 can be, for example, 1 μm to 100 μm, but is not particularly limited.

[0012] The phospholipid is not particularly limited, and a phospholipid having an isoelectric point of less than 7 when dispersed in water can be suitably used. The phospholipid preferably contains DOPS and does not contain DOPC and DSPE-MAL. In the technology of Patent Document 1, the substrate is coated with phospholipid by repeating alternating immersion of liposomes containing phospholipid and a compound having an isoelectric point of more than 7. However, as shown in FIG. 4 of Patent Document 1, in the liposome composition of Patent Document 1, the modification amount of the phospholipid is saturated at a certain number of immersions. In view of this situation, the composition of the phospholipid of the liposome is improved so that it contains DOPS and does not contain DOPC and DSPE-MAL, thereby increasing the number of immersions until the modification amount is saturated, and the amount of the coating layer containing the phospholipid can be increased. As the phospholipid, from the viewpoint of increasing the anionicity of the formed liposome (PSL) and increasing the loading amount of the coating layer, it is preferable that the phospholipid contains DOPS and DOPE-MAL, but does not contain DOPC. In this case, the molar ratio of DOPS:DOPE-MAL is preferably 40:60-60:40. DOPS, DOPE-MAL, and DOPC are the following compounds. DOPS: 1,2-Dioleoyl-sn-glycero-3-phospho-L-serine DOPE-MAL: Dioleoyl N-(3-Maleimide-1-oxopropyl)-L-α-phosphatidylethanolamine DOPC: 1,2-Dioleoyl-sn-glycero-3-phosphocholine

[0013] In a preferred embodiment, at least one compound selected from the group consisting of proteins and peptides is used. From the viewpoint of sufficiently forming the coating layer 5 by utilizing electrostatic adsorption, this compound has an isoelectric point of more than 7 when dispersed in water. The upper limit of the isoelectric point is 14. Specific examples of the at least one compound selected from the group consisting of proteins and peptides that can be suitably used include protamine (Pro), lysozyme (Lys), ribonuclease A (Rib), nisin (Nis), bone morphogenetic protein (BMP), basic fibroblast growth factor (FGF-2), transforming growth factor-β (TGF-β), and the like. The isoelectric point of proteins and peptides can be determined by referring to the value at the time of purchasing the reagent (the value published by the reagent manufacturer), but it can also be measured by two-dimensional electrophoresis. For identification of proteins and peptides, proteins and peptides are separated and extracted by two-dimensional electrophoresis, and if the accurate molecular weight can be determined by MALDI-TOF MS, they can be identified by searching the Mascot database. If the accurate molecular weight cannot be determined by MALDI-TOF MS, the protein or peptide is fragmented by trypsin digestion, and the molecular weight of the fragments is determined by MALDI-TOF MS and LC MS / MS, and the database Mascot is searched for identification.

[0014] 2. Manufacturing method of sheet 1 (1) Manufacturing method There is no particular limitation on the method for producing the sheet 1. A suitable example of the method for producing the sheet 1 is shown below. This manufacturing method uses a first liquid containing at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of greater than 7 when dispersed in water, and a second liquid containing liposomes formed from phospholipids. Then, the sheet base material 3 (collagen sheet) is alternately immersed in the first liquid and the second liquid.

[0015] (2) Specific examples of manufacturing methods (2.1) Synthesis of liposomes containing phospholipids The liquid containing liposomes synthesized by the method exemplified below becomes the second liquid. Here, as an example of the method for synthesizing liposomes, a method for synthesizing phosphatidylserine liposomes (PSL) will be described.

[0016] (2.1.1) Reagents The following reagents are used, for example: DOPS (NOF Corporation) DOPE-MAL (manufactured by NOF Corporation)

[0017] (2.1.2) Preparation of stock solutions Each reagent is dissolved in a chloroform / methanol mixed solvent (e.g., v / v=9 / 1) to a concentration of, for example, 10 mg / mL to prepare a stock solution. Each stock solution is stored at a low temperature (e.g., -30°C).

[0018] (2.1.3) Synthesis of PSL (phosphatidylserine liposome) The PSL is preferably a crosslinked type. An example of a method for synthesizing a crosslinked type PSL will be described. Here, a method for synthesizing a crosslinked phosphatidylserine liposome (crosslinked PSL) will be exemplified. An example of a method for preparing cross-linked phosphatidylserine liposomes (cross-linked PSL) is shown below. Each solution is added to a glass bottle so that the molar ratio is DOPS / DOPE-MAL = 50 / 50, and the solution is left to stand at room temperature overnight to evaporate the organic solvent and form a film. Bis-Tris buffer solution (100 mM, pH 7.1) is added so that the liposome concentration becomes a predetermined concentration (e.g., 10 mg / mL), and the liposomes are formed by ultrasonic treatment. The liposomes are filtered using polycarbonate membranes with pore sizes of 0.8 μm, 0.4 μm, 0.2 μm, 0.1 μm, and 0.05 μm. 500 μL of liposomes (10 mg / mL), 500 μL of calcium chloride (12 mM), and 20 μL of dithiothreitol (DTT, 73.5 mM) are mixed and left to stand at room temperature for 30 minutes to form cross-linked liposomes. A specific compound (DOPE-MAL) present in the liposome is crosslinked with dithiothreitol (DTT) to form a crosslinked phosphatidylserine liposome.

[0019] (2.1.4) Method for forming coating layer 5 (method for producing sheet 1) The coating layer 5 is preferably formed by alternately immersing the sheet substrate 3 in the first liquid and the second liquid. As the first liquid, an aqueous solution containing at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of more than 7 when dispersed in water, is preferably used. In order to utilize electrostatic interactions, it is preferable to alternately immerse the sheet substrate 3 in the second liquid, which is an aqueous solution containing anionic PSL, and the first liquid, which is an aqueous solution containing a cationic polymer, to form a coating layer 5, which is a mixed layer containing PSL and a polymer, on the sheet substrate 3. Note that the "cationic polymer" here refers to at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of more than 7 when dispersed in water. In this method, since PSL is negatively charged in an aqueous solution and protein or peptide is positively charged in an aqueous solution, the two are electrostatically adsorbed and bonded. By alternately immersing in two types of liquid, the negatively charged PSL and the positively charged protein or peptide are stacked (laminated) alternately to form a coating layer 5. In order to utilize the electrostatic adsorption between the PSL and the protein or peptide, the isoelectric point of the protein or peptide is preferably greater than 7 and less than 12 in pure water. If it is not greater than 7, electrostatic adsorption does not occur by alternate immersion, and a mixed layer is difficult to form on the substrate 3. If the isoelectric point of the protein or peptide is greater than 12, even if negatively charged PSL is stacked on a positively charged protein or peptide, the surface of the PSL will be positively charged due to the influence of the positive charge of the protein or peptide present below the PSL. Then, a repulsive force is generated between the positively charged surface of the PSL and the positively charged protein or peptide, and further stacking is not possible, and there is a risk that a sufficient coating layer 5 will not be formed. Therefore, the isoelectric point of the protein or peptide is preferably less than 12.

[0020] (2.1.5) Specific examples of methods for forming the coating layer 5 The following is a more specific example of a method for forming the coating layer 5. In this example, a substrate 3 having a negatively charged surface is used. Prepare an aqueous solution of protein or peptide (first solution, concentration: 0.5 mg / mL-2 mg / mL). Prepare an aqueous dispersion of PSL (second solution, concentration: 0.5 mg / mL-2 mg / mL). Then, the following steps A1, B1, and C1 are carried out in this order, and then, as necessary, B1 and C1 are alternately repeated. That is, each step is carried out in the order of A1, B1, C1 (B1, C1, C1). After the final step, a drying step may be carried out. [Step A1] The sheet substrate 3 is allowed to stand in a first solution at a predetermined temperature (e.g., 1° C.-40° C.) for a predetermined time (e.g., 1 hour-2 days) to adsorb proteins or peptides. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds-30 minutes) to remove unadsorbed proteins or peptides. [Step B1] The sheet substrate 3 is allowed to stand in the second solution at a predetermined temperature (e.g., 1°C to 40°C) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb PSL. The substrate 3 is then immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed PSL. [Step C1] The substrate 3 is allowed to stand in the first solution at a predetermined temperature (e.g., 1° C.-40° C.) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb the protein or peptide. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed protein or peptide.

[0021] If the surface of the substrate 3 is not charged, a step of positively or negatively charging the surface may be provided before the alternate immersion.

[0022] <Second embodiment> The sheet 1 of the second embodiment is a sheet including a collagen-containing sheet substrate 3 and a coating layer containing a phospholipid. The phospholipids contained are DOPS and DOPE-MAL, but not DOPC. In addition, the descriptions of the first embodiment apply mutatis mutandis to "collagen," "sheet base material 3," "coating layer 5," "DOPS," "DOPE-MAL," "DOPC," and "manufacturing method of sheet 1" in the sheet 1 of the second embodiment, and explanations of these are omitted. EXAMPLES

[0023] 1. Sheet Preparation In the examples, PSL was prepared without DOPC (see (1.1)), and an aqueous dispersion (second solution) was prepared using this PSL. An aqueous solution (first solution) of protamine was prepared separately. A sheet was produced using the first and second solutions. In the comparative example, PSL was prepared using DOPC (see (1.2)), and an aqueous dispersion (second solution) was prepared using this PSL. An aqueous solution (first solution) of protamine was prepared separately. A sheet was produced using the first and second solutions. Details are explained below.

[0024] (1) Preparation of PSL (1.1) Preparation of PSL without DOPC Each solution was added to a glass bottle so that the molar ratio was DOPS / DOPE-MAL=50 / 50, and the solution was left at room temperature overnight to evaporate the organic solvent and form a film. A Bis-Tris buffer solution (100 mM, pH 7.1) was added so that the liposome concentration was a predetermined concentration (e.g., 10 mg / mL), and liposomes were formed by ultrasonic treatment. The liposomes were filtered using polycarbonate membranes with pore sizes of 0.8 μm, 0.4 μm, 0.2 μm, 0.1 μm, and 0.05 μm. 500 μL of liposomes (10 mg / mL), 500 μL of calcium chloride (12 mM), and 20 μL of dithiothreitol (DTT, 73.5 mM) were mixed and left at room temperature for 30 minutes to form crosslinked liposomes. A specific compound (DOPE-MAL) present in the liposome was cross-linked with dithiothreitol (DTT) to form cross-linked PSL (cross-linked phosphatidylserine liposome). The PSL prepared in this section is called "PSL-A." DOPS: 1,2-Dioleoyl-sn-glycero-3-phospho-L-serine DOPE-MAL: Dioleoyl N-(3-Maleimide-1-oxopropyl)-L-α-phosphatidylethanolamine

[0025] (1.2) Preparation of PSL using DOPC The method for preparing PSL (crosslinked PSL) is shown below. Each solution was added to a glass bottle so that the molar ratio was DOPS / DOPC / DSPE-MAL = 30 / 20 / 50, and the solution was left to stand overnight at room temperature to evaporate the organic solvent and form a film. Under the same conditions as above (1.1), the solution was converted into liposomes by ultrasonic treatment and filtered. 500 μL of liposomes (10 mg / mL), 500 μL of calcium chloride (8 mM), and 20 μL of dithiothreitol (DTT, 73.5 mM) were mixed and left to stand at room temperature for 30 minutes to form crosslinked liposomes. The PSL prepared in this section is called "PSL-B". DOPS: 1,2-Dioleoyl-sn-glycero-3-phospho-L-serine DOPC: 1,2-Dioleoyl-sn-glycero-3-phosphocholine ·DSPE-MAL: Distearoyl N-(3-Maleimide-1-oxopropyl)-L-α-phosphatidylethanolamine

[0026] (1.3) Preparation of PSL-C Each solution was added to a glass bottle so that the molar ratio was DOPS / DOPC / DOPE-MAL = 30 / 20 / 50, and the solution was left at room temperature overnight to evaporate the organic solvent and form a film. The solution was converted into liposomes by ultrasonic treatment and filtered under the same conditions as in (1.1) above. 500 μL of liposomes (10 mg / mL), 500 μL of calcium chloride (20 mM), and 20 μL of dithiothreitol (DTT, 73.5 mM) were mixed and left at room temperature for 30 minutes to form crosslinked liposomes. The PSL prepared in this section is called "PSL-C." DOPS: 1,2-Dioleoyl-sn-glycero-3-phospho-L-serine DOPC: 1,2-Dioleoyl-sn-glycero-3-phosphocholine DOPE-MAL: Dioleoyl N-(3-Maleimide-1-oxopropyl)-L-α-phosphatidylethanolamine

[0027] (2) Sheet base material A collagen sheet (BIOMEND (registered trademark), manufactured by Zimmer-Bimet) was used as the sheet substrate. The collagen sheet was subjected to surface plasma treatment for 1 minute using a surface plasma treatment device. The conditions for the surface plasma treatment were a frequency of 50 kHz, power of 100 W, degree of vacuum of 0.05 T, and air flow rate of 10 sscm.

[0028] (3) Formation of the coating layer (3.1) Preparation of various solutions An aqueous solution of protamine (first solution, concentration: 1 mg / mL) was prepared. Salmon-derived protamine sulfate (isoelectric point: 10-12) from Sigma-Aldrich was used as the protamine. An aqueous dispersion of PSL-A (second solution, concentration: 1 mg / mL) was prepared. An aqueous dispersion of PSL-B (second solution, concentration: 1 mg / mL) was prepared.

[0029] (3.2) Preparation of sheets using PSL-A The following steps [Step A1], [Step B1] and [Step C1] were carried out in this order using an aqueous solution of protamine (first solution) and an aqueous dispersion of PSL-A (second solution). [Step A1] The substrate is left to stand in the first solution at a predetermined temperature (4°C) for a predetermined time (overnight) to adsorb protamine, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed protamine. [Step B1] The substrate is left in the second solution at room temperature (22 to 25°C) for a predetermined time (1 minute) to adsorb PSL, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed PSL. [Step C1] The substrate is left to stand in the first solution at room temperature (22 to 25°C) for a predetermined time (1 minute) to adsorb protamine, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed protamine. This series of operations was the first cycle. From the second cycle onwards, [Step B1] and [Step C1] were repeated as one cycle. That is, as described below, after the first cycle of [Step A1], [Step B1] and [Step C1], a set of [Step B1] and [Step C1] was repeated (prescribed cycle number - 1) times. After the final cycle, [Step A1] was repeated three times, and the substrate was dried by vacuum drying. 1st cycle: [Process A1] [Process B1] [Process C1] 2nd cycle: [Step B1] [Step C1] 3rd cycle: [Step B1] [Step C1] 4th cycle: [Step B1] [Step C1] .... nth cycle: [Step B1] [Step C1] Using the above procedure, the coating layer was formed for PSL-A at 30, 75, 150, and 400 cycles.

[0030] (3.3) Preparation of sheets using PSL-B A coating layer was formed in the same manner as in the case of PSL-A, except that an aqueous dispersion of PSL-B (second solution) was used, at 30 and 75 cycles.

[0031] 2. Measurement method and results (1) TEM observation When the sheet using PSL-A after 75 cycles was observed by TEM, it was confirmed that PSL was supported on the sheet, as shown in the TEM image in Figure 3. A periodic structure of about 4 nm was also observed in the PSL. Therefore, it is considered that the peak of the small-angle X-ray scattering is derived from this periodic structure. Note that this TEM image was observed using a sample that had been dried by vacuum drying after repeating [Step A1] three times after the final cycle, as described in Section 1.(3.2) above. In contrast, in the section "(1.1) TEM imaging and analysis" described below, a liposome aqueous solution is dropped onto a grid, rather than a sheet, for observation. (1.1) TEM Imaging and Analysis After the final cycle in section 1.(3.2) above, [Step A1] was repeated three times. After that, a sheet of PSL-A prepared without vacuum drying after 75 cycles was placed on a carbon-coated copper grid (#400), 2% phosphotungstic acid was dropped on it, and the sample was left to stand at 80°C for 10 seconds to image the sample. After the final cycle in section 1.(3.2) above, [Step A1] was repeated three times, and after that, a sheet of PSL-B prepared without vacuum drying after 75 cycles was placed on a carbon-coated copper grid (#400), 2% phosphotungstic acid was dropped on it, and the sample was left to stand at 80°C for 10 seconds to image the sample. After drying, the liposome structure was observed with a TEM (H-7600, Hitachi). Figure 4 shows an image of a typical TEM image of liposomes. In this image, the TEM image has been partially processed for easy understanding. A typical liposome structure was observed, in which multiple independent concentric structures equivalent to lipid bilayer membranes exist from the outermost layer of the spherical structure to the inner layer, and a hollow structure exists in the center. The lipid bilayer membranes were counted from the obtained TEM image to obtain the average number and distribution of membranes. The results are shown in Figure 5. Here, the "number of lipid bilayer membranes" means the number of membranes in a bilayer of phospholipids, and one white circle in the image represents one lipid bilayer membrane. In Figure 5, a sheet of PSL-A with 75 cycles is shown as an example, and a sheet of PSL-B with 75 cycles is shown as a comparative example. In addition, using Image J (NIH), the radius of the entire liposome and the radius of the hollow part inside the liposome were measured, and then the volume of the entire liposome and the volume of the hollow part were calculated. The results are shown in Figure 6 as a percentage of the volume of the hollow part. (1.2) Analysis results The number of lipid bilayer membranes per liposome in the Comparative Example and the Example was 3.5 and 6.1 on average, respectively, and the average cavity volume percentage was 55 vol.% and 4 vol.%, respectively, and it was found that the liposome in the Example had a structure with a greater number of lipid bilayer membranes and a smaller cavity portion. Figure 7 shows an image of the multilamellar liposome structure. Generally, liposomes are unstable because they have a single lipid bilayer membrane at the outermost layer and a structure with a large cavity, and when they are adsorbed onto the carrier surface during the immersion cycle process, the structure is destroyed, making it impossible to stack the liposomes and resulting in no increase in the loading amount. Compared to the comparative example, the liposomes of the examples have higher structural stability due to an increase in the number of lipid bilayer membranes and a decrease in the volume of the cavity. Therefore, the structure destruction during adsorption onto the carrier surface can be suppressed. For this reason, it is presumed that the number of cycles required for the liposomes of the examples to reach saturation of the loading amount increased, and the maximum loading amount increased significantly. (2) Method for measuring the amount of liposomes supported on the substrate and the measurement results (2.1) Method for measuring liposome amount The substrate with a coating layer of liposomes containing fluorescent lipid F-DHPE was immersed in 2 mL of solution x (2% Triton X-100, 2 M sodium chloride, 100 mM Tris-HCl, pH 7.5) and stirred overnight at 200 rpm in the dark to detach the fluorescent liposomes from the substrate. The fluorescence intensity of the solution was measured with a plate reader (excitation filter 485 nm, emission filter 530 nm). The liposome concentration in the solution was determined from a calibration curve of liposome solutions of known concentrations, and the amount of liposomes supported on the substrate was calculated. (2.2) Measurement results of liposome amount The results of quantifying the amount of liposome modification are shown in FIG. 8. In any liposome, the amount of liposome modification increased with increasing the number of stackings, and reached a plateau at a certain number of stackings. The amount of liposome modification relative to the number of stackings increased in the order of PSL-A, PSL-C, and PSL-B. (Patent Document 1) In the liposome composition (PSL-B) shown in JP-A-2022-94503, the amount of modification reached a plateau of 108 μg / cm2 at 75 cycles, as in FIG. 4 of (Patent Document 1). In PSL-A, the amount of modification reached a plateau of 1335 μg / cm2 at 400 cycles, and in PSL-C, the amount of modification reached a plateau of 249 μg / cm2 at 100 cycles. By improving the lipid composition, the number of immersions until the amount of modification reached saturation could be increased, and the amount of the coating layer containing phospholipids could be increased. This increase in the amount of modification correlates with an increase in the number of lipid bilayer membranes of the liposome and a decrease in the cavity volume, i.e., can be explained from the viewpoint of the structural stability of the liposome. Generally, liposomes are unstable because they have a single lipid bilayer membrane in the outermost layer and a structure with a large cavity, and in the immersion process, when the liposomes are adsorbed onto the carrier surface, the structure is destroyed, and the liposomes can no longer be stacked, so that the amount of the liposomes carried does not increase. As mentioned above, compared to PSL-B, PSL-A and PSL-C are (presumably) more structurally stable due to an increase in the number of lipid bilayer membranes and a decrease in the volume of the cavity. This makes it possible to suppress the destruction of the structure that occurs during adsorption to the support surface. In particular, PSL-A, which has the largest number of lipid bilayer membranes and the smallest cavity volume, significantly increased the number of immersion times required to reach saturation of the loading amount, and as a result, the maximum loading amount increased significantly.

[0032] (3) Small angle X-ray scattering measurements (3.1) Calculation of strength value by formula (I) Small-angle X-ray scattering, in which X-rays are irradiated onto a sample and X-rays scattered in the low-angle region of 2θ<10° or less are observed, can evaluate periodic structures in the range of a few nanometers to a few tens of nanometers. Sheets of 30, 75, 150, and 400 cycles made using PSL-A were measured at the small-angle X-ray scattering beamline / BL8S3 of the Aichi Synchrotron Light Center (a synchrotron radiation facility). The measurement conditions were: incident X-ray wavelength: 0.92 Å (13.5 keV), camera length: 4.0 m, beam diameter: 1.0 × 0.5 mm, measurement wavenumber region q (nm -1 ): 0.0-2.5. The standard sample, glassy carbon (NIST-3600), and no sample (air scattering) were measured under the same conditions as the collagen sheet. In small-angle X-ray scattering, the wavenumber region q (nm -1A maximum peak in scattering intensity attributed to PSL was detected at a position of λ = 1.31 (see Figure 2). The intensity value of the maximum peak in small-angle X-ray scattering depends on the measurement conditions (wavelength and integration time) and the instrument. In order to eliminate the influence of these parameters and simply correlate the intensity value with the amount of PSL supported, the intensity values ​​of the sheets at 30, 75, 150, and 400 cycles were calculated by the following formula (I) using the data of glassy carbon (NIST-3600) and no sample. Intensity value = (Is - Is bg )÷(I G -I0) × 100000 ... Formula (I) Is: q (nm -1 Scattering intensity at Is bg : q (nm -1 )=1.31 I G q (nm) when glassy carbon is used as the measurement sample -1 Scattering intensity at I0: q (nm -1 Scattering intensity at Here, Is bg is the scattering intensity distribution when a sheet is used as a measurement sample, and q (nm -1 )=1.0 and q(nm -1 ) = 1.6, and the line is connected to q(nm -1 )=1.31.

[0033] The strength values ​​of the sheet at 30, 75, 150, and 400 cycles at q=1.31 were 212, 879, 2845, and 11361, respectively, and the strength increased with increasing number of cycles. From this result, it was found that the loading amount was not saturated up to 400 cycles in the case of PSL-A. Compared with PSL-B, in the case of PSL-A, the number of lipid bilayers per liposome increased and the percentage of void volume in the liposome also decreased, which resulted in suppression of liposome dissociation, and therefore it is presumed that the increased loading amount was observed up to 400 cycles.

[0034] The strength values ​​at the position q = 1.31 were also measured for the sheets using PSL-B after 30 and 75 cycles in the same manner. The strength values ​​were 19 and 42, respectively, which were lower than the values ​​for the sheets using PSL-A after 30 and 75 cycles. Similarly to PSL-B, DOPS, DOPC, DSPE-MAL, and the fluorescent lipid Fluorescein DHPE were used to prepare fluorescently modified PSL-B' with a molar ratio of DOPS / DOPC / DSPE-MAL / Fluorescein DHPE=29.1 / 19.4 / 48.5 / 3.0. Sheets were prepared for 30, 50, 75, and 100 cycles in the same manner as in the case of PSL-B. The loading amount of each sheet using PSL-B' was 56 μg / cm. 2 ,72μg / cm 2 ,108μg / cm 2 ,125μg / cm 2 The loading amount was nearly saturated after about 100 cycles. Generally, liposomes have a single lipid bilayer (one membrane) and a large cavity that contains solvent molecules, and therefore are easily dissociated on the substrate. Therefore, in the sheet using PSL-B', the growth of the coating layer cannot be expected due to this dissociation, and it is considered that liposomes are difficult to be loaded. In the case of PSL-B' using DOPC and DSPE-MAL, the growth of the coating layer cannot be expected and the loading amount of the coating layer is low, so for the same reason, it is presumed that the loading amount of the coating layer will also be low in the case of PSL-B using DOPC and DSPE-MAL.

[0035] (3.2) Calculation of strength value by formula (II) In the above (1.1) column, the strength value is calculated using formula (I). In this column, the strength value is calculated using the following formula (II). The procedure is the same as in (1.1) except that formula (II) is used. Specifically, 30, 75, 150, and 400 cycle sheets made using PSL-A were measured at the small angle X-ray scattering beamline / BL8S3 of the Aichi Synchrotron Radiation Center (a synchrotron radiation facility). The measurement conditions were: incident X-ray wavelength: 0.92 Å (13.5 keV), camera length: 4.0 m, beam diameter: 1.0 × 0.5 mm, measurement wave number range q (nm -1 ): 0.0-2.5. The standard sample, glassy carbon (NIST-3600), and no sample (air scattering) were measured under the same conditions as the collagen sheet. In small-angle X-ray scattering, the wavenumber region q (nm -1 A maximum peak in scattering intensity attributed to PSL was detected at the position of λ = 1.31. The intensity value of the maximum peak in small-angle X-ray scattering depends on the measurement conditions (wavelength and integration time) and the instrument. In order to eliminate the influence of these parameters and simply correlate the intensity value with the amount of PSL supported, the intensity values ​​of the sheets at 30, 75, 150, and 400 cycles were calculated by the following formula (II) using the data of glassy carbon (NIST-3600) and no sample. Intensity value = (Is-I0) ÷ (I G -I0)×100000 …Formula (II) Is: q (nm -1 Scattering intensity at I G q (nm) when glassy carbon is used as the measurement sample -1 Scattering intensity at I0: q (nm -1 Scattering intensity at

[0036] The strength values ​​of the sheet at 30, 75, 150, and 400 cycles at the position q = 1.31 were 226, 888, 2859, and 11395, respectively, and the strength increased with increasing number of cycles.

[0037] The strength values ​​at the position q = 1.31 were also measured for the sheets using PSL-B after 30 and 75 cycles in the same manner. The strength values ​​were 36 and 65, respectively, which were lower than the values ​​for the sheets using PSL-A after 30 and 75 cycles.

[0038] 3. Summary of experimental results The sheets of the examples using PSL-A, whether using formula (I) or formula (II), had a q (nm -1 It was found that the intensity value of the peak at 0.01 μm=1.31 was greater than 100, and the amount of the coating layer containing phospholipids was high. Therefore, the sheet of the example is expected to have high tissue repair properties.

[0039] <Other embodiments (modifications)> Incidentally, the present invention is not limited to the above examples and embodiments, and can be embodied in various forms without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0040] 1...Sheet 3...Sheet base material 5…Covering layer 7. Liposomes 9...At least one compound selected from the group consisting of proteins and peptides

Claims

1. A sheet substrate containing at least one selected from the group consisting of collagen and collagen derivatives; A sheet comprising a coating layer containing a phospholipid, In small angle X-ray scattering measurements, the wave number region q (nm -1 ) has a maximum peak of scattering intensity in the range of 1.2<q<1.4, A sheet having a strength value defined by the following formula (I) greater than 100 and less than 12,000. Intensity value=(Is-Is bg )÷(I G -I 0 ) × 100000 ... Formula (I) Is: Scattering intensity at the maximum peak in the range of 1.2<q<1.4 when a sheet is used as a measurement sample I bg : Background scattering intensity at the same q as the maximum peak of the sheet when a sheet is used as a measurement sample I G Scattering intensity at the same q as the maximum peak of the sheet when glassy carbon is used as a measurement sample I 0 : Scattering intensity at the same q as the maximum peak of the sheet when no measurement sample is placed

2. The sheet according to claim 1, comprising DOPS and DOPE-MAL as the phospholipids.

3. A sheet substrate containing at least one selected from the group consisting of collagen and collagen derivatives; A sheet comprising a coating layer containing a phospholipid, A sheet comprising, as the phospholipid, DOPS and DOPE-MAL, but not DOPC or DSPE-MAL.

4. The phospholipids include DOPS and DOPE-MAL, The molar ratio of the DOPS:DOPE-MAL is 40:60-60:

40.

5. The sheet according to claim 1 or 3, wherein the phospholipids form crosslinked liposomes.

6. The coating layer is 4. The sheet according to claim 1, which contains at least one compound selected from the group consisting of proteins and peptides having an isoelectric point of more than 7 when dispersed in water.

7. The sheet according to claim 6 , wherein the coating layer contains protamine as the protein.

Citation Information

Patent Citations

  • Implant material, and method for producing implant material

    JP2022094503A